Humanitarian intervention and human rights - Alkhattab REEM (Studia Universitatis Babeș-Bolyai. Philosophia)
We are living in the “era of human rights,” with increasing attention to them following the Universal Declaration of Human Rights. Humanitarian interventions are mechanisms aimed to protecting human rights and reducing suffering, yet they pose ethical challenges due to the use of lethal force and its resulting harm to civilians.